Analyze the Effectiveness of Resource Mobilizations of Local Government - Kharel, Khom Raj; Kharel, Suman (Management Dynamics, 2020)
Local governments are the closest administrative units which deliver public services to the grassroots level of citizens. Local governments enhance the access of services to the citizens. Effectiveness of budget implementation depends on the absorptive capacity of local governments and local level transparency in their affairs. The effectiveness of budget implementation is measured in terms mobilization of local resources and development of surrounding. Through the local resource mobilization, countries accelerate their economic growth by raising and spending their own funds for public goods and services such as schools, hospitals, clean water, electricity and roads. Local government investment in their own public goods and services in infrastructure is also essential for attracting private investment and laying the foundation of long term economic growth. The Constitution of Nepal 2015 defines Nepal as a federal democratic republic organized three level governments as federal, province and local. Local governments are the development partners to the central government need to mobilize enough revenue locally to support the central government development agenda. Inadequate financial resources can undermine the effective implementation of developmental projects in Nepal. Budgets are important as they prudential manage scarce financial resources and at the same time serve as a means of expenditure authorization, control and evaluation base.